Joy : poet, seeker, and the woman who captivated C. S. Lewis - Santamaria, Abigail (Boston : Houghton Mifflin Harcourt, 2015)
"The first full biography of Joy Davidman, known primarily as C.S. Lewis's late-in-life bride, but who here receives her much deserved rescue from that shadow"--
1892-1930 -- 1930-1934 -- 1934-1938 -- 1938-1939 -- June-December 1939 -- 1939-1942 -- 1942-1944 -- 1944-1946 -- 1946-1950 -- 1950-1952 -- August 1952-January 1953 -- January-November 1953 -- November 1953-April 1954 -- Fall 1954-October 1956 -- Fall 1956-Fall 1957 -- 1958-1960.
Includes bibliographical references (pages 391-395) and index.
Keywords: Davidman, Joy; Women poets, American -- Biography; Authors' spouses -- Great Britain -- Biography; Christian converts from Judaism -- United States -- Biography